Dynamics of the Apostichopus californicus-associated flavivirus under suboxic conditions and organic matter amendment - Crandell, Jameson G.; Altera, Ashley K.; DeRito, Christopher M.; Hebert, Kyle P.; Lim, Em G.; Markis, Joel; Philipp, Katherine H.; Rede, Jordan E.; Schwartz, Megan; Vilanova-Cuevas, Brayan; Wang, Evangeline; Hewson, Ian (Frontiers in Marine Science, 2023)
Flaviviruses cause some of the most detrimental vertebrate diseases, yet little is known of their impacts on invertebrates. Microbial activities at the animal-water interface are hypothesized to influence viral replication and possibly contribute to pathology of echinoderm wasting diseases due to hypoxic stress. We assessed the impacts of enhanced microbial production and suboxic stress on Apostichopus californicus associated flavivirus (PcaFV) load in a mesocosm experiment. Organic matter amendment and suboxic stress resulted in lower PcaFV load, which also correlated negatively with animal mass loss and microbial activity at the animal-water interface. These data suggest that PcaFV replication and persistence was best supported in healthier specimens. Our results do not support the hypothesis that suboxic stress or microbial activity promote PcaFV replication, but rather that PcaFV appears to be a neutral or beneficial symbiont of Apostichopus californicus.